2021
DOI: 10.30682/nm2103g
|View full text |Cite
|
Sign up to set email alerts
|

Financing agri-food business in the Mediterranean area through crowdfunding: Do environmental issues matter?

Abstract: Global expectations are that crowdfunding will be able to unleash the great potential for contributing to sustainable development by providing financial resources for environmentally and socially oriented ven-tures. The purpose of this paper is to estimate which factors, including the orientation to sustainability, foster the likelihood of crowdfunding success in agri-food campaigns. Using a sample of crowdfunding campaigns launched in the Kickstarter platform, this paper employs a binary logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…They discovered that enhancing publicity, reducing the investment threshold and increasing the benefits of a crowdfunding campaign can increase the decision weight assigned to a campaign and favor rapid investment decisions. Ljumović et al. (2021) examined the success factors of agri-food crowdfunding campaigns launched on the Kickstarter platform.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They discovered that enhancing publicity, reducing the investment threshold and increasing the benefits of a crowdfunding campaign can increase the decision weight assigned to a campaign and favor rapid investment decisions. Ljumović et al. (2021) examined the success factors of agri-food crowdfunding campaigns launched on the Kickstarter platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the relevance of crowdfunding in the food sector, only a few academic studies have examined this line of research (Pronti and Pagliarino, 2019;Troise et al, 2021). Some have investigated the determinants of crowdfunding campaign performance (Li et al, 2020;Ljumovi c et al, 2021;Kocollari et al, 2022), whereas others have examined the potential of crowdfunding in the food sector (Yoo and Choe, 2014;Misso et al, 2017;Cillo et al, 2019;Pronti and Pagliarino, 2019;Troise et al, 2021). However, although numerous studies exist on crowdfunding in the food sector, studies on vegan crowdfunding is nonexistent despite its significance in the vegan community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crowdfunding can be a helpful way to fund organic farming, as it is environmentally friendly, and backers support environmentally conscious agribusinesses (Ljumović et al, 2021). Giakoumelou et al (2023) found that the number of images, comments, updates and the readability of the project description positively impact the success rate of vegan crowdfunding campaigns, while the length of the description of the project has a negative effect.…”
Section: Introductionmentioning
confidence: 99%